Cyclopentolate eye drops-induced anaphylaxis in an infant - Terece, Sinem Polat; Ertoy-Karagöl, Hacer İlbilge; Köken, Gizem; Atalay, Hatice Tuba; Türkcan, Büşra Topuz; Vural, Özge; Bakırtaş, Arzu (The Turkish Journal of Pediatrics, 2022)
Background. Cyclopentolate is frequently used as a mydriatic agent during ophthalmological examinations in childhood and hypersensitivity reactions associated with this drug are rare. We aim to report an infant who experienced anaphylaxis due to cyclopentolate eye drops. Case. A nine-month-old girl, who was being followed up with a diagnosis of retinoblastoma, presented for consultation for urticaria, cough, stridor, and dyspnea that developed after the administration of topical cyclopentolate to the eyes. The patient was diagnosed with anaphylaxis and treated with adrenaline. During the follow-up, tropicamide was used safely as an alternative drug. Conclusions. In children, hypersensitivity reactions due to cyclopentolate are very rare. Only four pediatric patients were reported in the literature to have developed an allergic reaction after the administration of cyclopentolate eye drops. We present here the youngest patient who developed anaphylaxis with cyclopentolate eye drops. Anaphylaxis due to cyclopentolate should be kept in mind, rapidly recognized, and treated when a reaction develops.
Keywords: anaphylaxis; children; cyclopentolate; eye drop; mydriatic